Big Five Personality, Ethical Sensitivity, and Performance of Auditors - Dewi, I Gusti Ayu Agung Pradnya; Dewi, Putu Purnama (International Research Journal of Management, IT & Social Sciences, 2018)
This study aimed to examine and to obtain empirical evidence on the effect of Ethical Sensitivity on the Auditors Performance and the influence of moderation of Big Five Personality on the relationship between the Ethical Sensitivity and Performance of Auditors of the Public Accountant Offices in Bali. The study used primary data sources and the data types used were quantitative data, collected through questionnaires. Data analysis technique used was Moderated Regression Analysis (MRA) approach. The results obtained in the study is the ethical sensitivity has a positive effect on the auditorsâ performance and personality traits contained in the Big Five Personality model which can strengthen the relationship between ethical sensitivity and the auditorsâ performance. Auditors who have the personalities of extraversion, agreeableness, conscientiousness, emotional stability and openness to experience tend to remain ethical even in the face of a pressing ethical dilemma that they are able to provide optimal performance.